Answer:
Value of z is 3/8.
Explanation:
Given:
![((1)/(4))^(3z-1)=16^(z+2)*64^(z-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2yx4zimpd34x2au0sujvwq158e0pqou4cz.png)
We need to solve the given expression.
Consider,
![((1)/(4))^(3z-1)=16^(z+2)*64^(z-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2yx4zimpd34x2au0sujvwq158e0pqou4cz.png)
![((1)/(2^2))^(3z-1)=(2^4)^(z+2)*(2^6)^(z-2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q8eq2m6gfw42mqkwrtb0uuf33stzvnyemb.png)
Now, using law of exponent
![(x^a)^b=x^(ab)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o6tm02hk2df945y66lhsgceqa4tbgtsevu.png)
![(((1)/(2))^2)^(3z-1)=(2)^(4(z+2))*(2)^(6(z-2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/u14co1i1io9wv30z1yhjmowl39ac986mik.png)
![((1)/(2))^(2(3z-1))=2^(4(z+2))*2^(6(z-2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/17hn2or966h3hfo8czxmm41ew8bfg4btzx.png)
Now using Result of Exponent on LHS
![x^(-a)=((1)/(x))^a](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cchdo94u2ldqu6iofumiq3rouqjrxydlji.png)
![2^(-2(3z-1))=2^(4(z+2))*2^(6(z-2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xifab3a1ahx5v560e6yme3wruv8w5q0vsp.png)
Now using another law of exponent on RHS,
![x^a* a^b=x^(a+b)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/q71ycpc6m4wfw3qk1qbv34nk20ohjpmz3u.png)
![2^(-2(3z-1))=2^(4(z+2)+6(z-2))](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ipmxe1nuj9i1kpw71k99xrje2leqbpgi4n.png)
![2^(2-6z)=2^(4z+8+6z-12)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2167yraula9t022rsoi0x0pbn34imj26x4.png)
![2^(2-6z)=2^(10z-4)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ykky43qj9hcjz4duxnlnmk4dbexinotd3y.png)
By comparing Exponent of both sides, we get
2 - 6z = 10z - 4
2 + 4 = 10z + 6z
16z = 6
z = 6/16
z = 3/8
Therefore, Value of z is 3/8.